Anatomical Demonstration of Ocular Dominance Columns in Striate Cortex of the Squirrel Monkey - Horton, Jonathan C. (J Neurosci, 1996)
The squirrel monkey is the only primate reported to lack ocular dominance columns. Nothing anomalous about the visual capacity of squirrel monkeys has been found to explain their missing columns, leading to the suggestion that ocular dominance columns might be “an epiphenomenon, not serving any purpose” (Livingstone et al., 1995). Puzzled by the apparent lack of ocular dominance columns in squirrel monkeys, we made eye injections with transneuronal tracers in four normal squirrel monkeys. An irregular mosaic of columns, averaging 225 μm in width, was found throughout striate cortex. They were double-labeled by placing wheat germ agglutinin-horseradish peroxidase into the left eye and [(3)H]proline into the right eye. The tracers labeled opposite sets of interdigitating columns, proving they represent ocular dominance columns. The columns were much clearer in layer IVcα (magno-receiving) than IVcβ (parvo-receiving). In the lateral geniculate body, the parvo laminae showed extensive mixing of ocular inputs, suggesting that increased label spillover contributes to the blurred columns in layer IVcβ. The cytochrome oxidase (CO) patches were organized into distinct rows, but they bore no consistent relationship to the ocular dominance columns. These experiments indicate that ocular dominance columns are less well segregated in squirrel monkeys than macaques, but they are present. This fact is pertinent to a recent study reporting that ocular dominance columns are absent in normal squirrel monkeys, but induced to form by strabismus (Livingstone, 1996).